2014
DOI: 10.1186/s12929-014-0086-y
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Lactobacillus plantarum expressing and secreting heterologous oxalate decarboxylase prevents renal calcium oxalate stone deposition in experimental rats

Abstract: BackgroundCalcium oxalate (CaOx) is the major constituent of about 75% of all urinary stone and the secondary hyperoxaluria is a primary risk factor. Current treatment options for the patients with hyperoxaluria and CaOx stone diseases are limited. Oxalate degrading bacteria might have beneficial effects on urinary oxalate excretion resulting from decreased intestinal oxalate concentration and absorption. Thus, the aim of the present study is to examine the in vivo oxalate degrading ability of genetically engi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 34 publications
1
28
0
4
Order By: Relevance
“…LAB administered rats showed normal morphology of renal tissue and decreased crystal deposition compared to rats fed with KOx. The obtained result suggests that colonization of administered LAB consumes intestinal oxalate that leads to decreased crystal deposition in kidney, this is similar with previous studies (Kwak et al, 2006;Sasikumar et al, 2014). Mild inflammation and reduced crystal deposition in QE treated rats revealed that oxalate toxicity is reduced by the antioxidant action of quercetin.…”
Section: Discussionsupporting
confidence: 93%
“…LAB administered rats showed normal morphology of renal tissue and decreased crystal deposition compared to rats fed with KOx. The obtained result suggests that colonization of administered LAB consumes intestinal oxalate that leads to decreased crystal deposition in kidney, this is similar with previous studies (Kwak et al, 2006;Sasikumar et al, 2014). Mild inflammation and reduced crystal deposition in QE treated rats revealed that oxalate toxicity is reduced by the antioxidant action of quercetin.…”
Section: Discussionsupporting
confidence: 93%
“…The correction of these abnormalities by L. helveticus and L. plantarum supplementation could be valuable in prevention of the disease. Previously, it has been demonstrated that probiotic therapy with L. plantarum strains improves urinary oxalate, calcium, uric acid, creatinine and serum uric acid levels in rats with increased renal calcium oxalate deposition [35]. A diet rich in fructose can lead to the induction of marked oxidative stress and mitochondrial dysfunction [36].…”
Section: Discussionmentioning
confidence: 99%
“…The subsequent formation of CaOx crystals may account for kidney stone formation. As proposed previously, hyperoxaluria is considered a major risk factor for urinary stone, and experimental induction of hyperoxaluria can lead to crystalluria and CaOx crystal deposition in the kidney [6,7]. In addition, recurrent idiopathic stone formers always show mild hyperoxaluria; meanwhile, amount and size of CaOx crystals, alongside disease severity, are highly related to urinary excretion of oxalate (Ox) [8].…”
Section: Introductionmentioning
confidence: 97%